Rural development through Islamic banks - Khan, Mohammad Akram, 1926-; Islamic Foundation (Great Britain). (Leicester : Islamic Foundation, 1994)
Suggesting a number of proposals to provide interest-free finance for rural development, this text shows how Islamic banks can play an active role in improving the lot of the rural poor.
&#x000A
Includes bibliographical references [p. 60-62].
&#x000A
oif 23/06/14
Loan
Keywords: Economic development -- Developing countries. Rural development -- Developing countries -- Finance. Banks and banking -- Religious aspects -- Islam. Banks and banking -- Islamic countries. Rural credit -- Islamic countries; Economics. &#x000A